Preparation, characterization and functional properties of flax seed protein isolate. (15th April 2016) - Kaushik, Pratibha; Dowling, Kim; McKnight, Stafford; Barrow, Colin J.; Wang, Bo; Adhikari, Benu
Highlights: Flaxseed protein isolate with 90% purity was obtained by demucilaging the seeds at 60 °C. Amino acid profile of extracted protein was identified and compared with a selection of commonly used proteins. FPI has lower solubility but better thermal stability than other oilseed proteins. Zeta-potential, EAI and ESI of FPI stabilised emulsion was more than the WPI, SPI, Gel and SC stabilised emulsions. Functional properties of FPI such as WAC, FAC and EDS were comparable to the best known protein emulsifiers. Abstract: Flaxseed protein isolate (FPI) was extracted from flaxseeds, and its amino acid composition and functional properties (solubility, thermal stability, emulsifying properties and electrostatic charge density, water holding and fat absorption capacities) were determined. The highest purity of FPI (90.6%) was achieved by extraction at 60 °C. FPI had a low lysine to arginine ratio of 0.25, which is desired in heart-healthy foods and infant formulas. The denaturation temperature of FPI was 105 °C. FPI had the highest emulsion activity index (375.51 m 2 /g), highest emulsion stability index (179.5 h) and zeta potential (−67.4 mV) when compared to those of other commonly used proteins, such as sodium caseinate (SC), whey protein isolate (WPI), gelatin (Gel) and soy protein isolate (SPI). The average emulsion droplet size of emulsions stabilized by these proteins was in the order SC < FPI < WPI < Gel < SPI. Water holding and fat absorption capacities of FPI were similar to those of the above mentioned proteins.